THE IMAGE OF GLOBAL VEILED WOMEN: MULTIMODAL DISCOURSE ANALYSIS OF BUTTONSCARVES ADVERTISEMENTS - Husnul Waro'i, Muhammad Rosyid; Ascalonicawati, Adinda Prasty; Billah, Zakiyah Dania (Metahumaniora, 2026)
This study examines how multimodal discourse in Instagram advertisements constructs representations of global veiled women within Indonesia’s contemporary modest fashion industry. Using Kress and van Leeuwen’s (2006) multimodal discourse analysis framework, the research analyzes three Instagram video advertisements from the Buttonscarves x Indah Nada Puspita collaboration. The analysis focuses on three semiotic dimensions: linguistic features (song lyrics and written text), visual-verbal interplay (composition, color, setting, and body language), and the representational strategies of the global veiled women. Findings reveal that these advertisements construct Muslim womanhood at the intersection of religious piety, global consumerism, and local cultural identity, operating within what scholars term the “piety economy” where religious expression and commodity consumption are mutually reinforcing. The advertisements employ neo-colonial perspective by situating Indonesian Muslim women within Western cultural settings and musical frameworks, yet simultaneously demonstrate cultural hybridization whereby veiled women assert their right to participate in transnational flows of fashion, romance, and tourism without sacrificing religious authenticity. The study also finds that the three advertisements collectively challenge Western stereotypes while constructing normative standards of middle-class, urban, educated Muslim femininity. This research contributes to understanding how commercially social media participates in negotiating Muslim identity, gender representation, and globalization in contemporary Indonesia.